Human peripheral blood derived mesenchymal stem cells demonstrate similar characteristics and chondrogenic differentiation potential to bone marrow derived mesenchymal stem cells - Chong, P.P.; Selvaratnam, L.; Abbas, A.A.; Kamarul, Tunku (2011)
The use of mesenchymal stem cells (MSCs) for cartilage repair has generated much interest owing to their multipotentiality. However, their significant presence in peripheral blood (PB) has been a matter of much debate. The objectives of this study are to isolate and characterize MSCs derived from PB and, compare their chondrogenic potential to MSC derived from bone marrow (BM). PB and BM derived MSCs from 20 patients were isolated and characterized. From 2ml of PB and BM, 5.4 +/- 0.6 million and 10.5 +/- 0.8 million adherent cells, respectively, were obtained by cell cultures at passage 2. Both PB and BM derived MSCs were able to undergo tri-lineage differentiation and showed negative expression of CD34 and CD45, but positively expressed CD105, CD166, and CD29. Qualitative and quantitative examinations on the chondrogenic potential of PB and BM derived MSCs expressed similar cartilage specific gene (COMP) and proteoglycan levels, respectively. Furthermore, the s-GAG levels expressed by chondrogenic MSCs in cultures were similar to that of native chondrocytes. In conclusion, this study demonstrates that MSCs from PB maintain similar characteristics and have similar chondrogenic differentiation potential to those derived from BM, while producing comparable s-GAG expressions to chondrocytes. (C) 2011 Orthopaedic Research Society. (C) 2011 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 30:634642, 2012